Challenges in the crystal growth of Li2FeSiO4 - Hergett, Waldemar; Neef, Christoph; Meyer, Hans-Peter; Klingeler, Rüdiger (Journal of crystal growth, 2021)
The high-pressure optical floating-zone method enables single crystal growth of the Pmnb high-temperature phase of Li2FeSiO4. The influence of growth conditions on crystal quality, phase homogeneity, and impurity formation in Li2FeSiO4 is studied. The use of different starting materials, i.e., either the P121/n1 or the Pmn21 polymorph, as well as optimization of various growth conditions is investigated. Several mm3-sized high-quality single crystals are obtained by the choice of the Pmn21 polymorph as the starting material. A general challenge of Li2FeSiO4 crystal growth is polymorph control during crystallization. While the temperature gradient at the solid-liquid interface seems to have significant impact on stabilizing the Pmnb high-temperature phase, growth velocity has no evident effect.